Development and validation of scales measuring individual, nursing unit, hospital, and community factors related to fertility intentions of female Japanese hospital nurses - Kiyoko Abe; Mayumi Nitta; Kuniko Chiba; Sachiko Tsujita; Yukiko Takada; Miki Sasaki; Mamiko Furuya (BMC Women's Health)
Abstract Background Scales that comprehensively measure individual, workplace, and community factors related to fertility intentions of women are limited. This study examined the psychometric properties of scales measuring individual (nurse, husband/partner, and child), nursing unit, hospital, and community factors related to fertility intentions of female Japanese hospital nurses. We focused on these nurses because nursing is a gendered profession, and over 90% of nurses in Japan are women. Furthermore, Japanese hospital nurses differ from other female workers in several ways (e.g., professionality, working shifts, financial remuneration). Methods This was a methodological study. Data were collected using a cross-sectional, self-administered questionnaire survey. Data from 898 Japanese female hospital nurses (age range, 20–49 years) from 50 hospitals were analyzed. The initial scales were developed through semi-structured interviews, a literature review, an expert review, and a pilot study. Item analysis and exploratory and confirmatory factor analyses were performed, Cronbach’s α was calculated, and known group validity was examined. Results The following individual factor scales were obtained: a 12-item, four-domain nurse factor (Economic Needs, Timing of Life Events, Nursing Aspirations, and Career Development) scale, a six-item, two-domain husband/partner factor (Share of Housework and Childcare and Relationship with Husband/Partner) scale, and a three-item, one-domain child factor scale. Likewise, we identified a 13-item, four-domain nursing unit factor (Guilty Feelings toward Colleagues, Unit Nurse Manager’s Management, Workability, and Collegiality) scale, a nine-item, three-domain hospital factor (Access to Legal Rights, Support for Mothers, and Comfort in Hospitals) scale, and a six-item, two-domain community factor (Governmental Family Support and Culture of Working Women) scale. Except for the child factor scale, the comparative fit index was > 0.950, and the root mean square error of approximation was < 0.070. Cronbach’s α ranged from 0.590 (community factor scale) to 0.807 (child factor scale). The scores on the nurse, husband/partner, and hospital factor scales were significantly higher for nurses with high than with low fertility intentions. Conclusions These results support the reliability and validity of the nurse, husband/partner, and hospital factor scales. The child, nursing unit, and community factor scales can be further improved.